2011
DOI: 10.3390/molecules16065054
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Lowering Activity of the Major Polyphenols in Grape Seed

Abstract: The major polyphenols in grape seed have been shown to have beneficial health effects in the prevention of dyslipidemia and cardiovascular diseases. In this present study, we investigated the cholesterol-lowering activity of three major polyphenolic compounds found in grape seed. The results showed that gallic acid, catechin, and epicatechin significantly inhibited pancreatic cholesterol esterase in a concentration-dependent manner. Moreover, they bound to taurocholic acid, taurodeoxycholic acid, and glycodeox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 22 publications
5
117
0
Order By: Relevance
“…These effects can be due to the combination of GS oil available to decreased absorbed crude fat. Also, Benzie (2003) and Ngamukote et al (2011) Abdallah et al (2017 who reported that GS extract has plenty of antioxidant substances that have decreasing effect on LDL and increasing effect on HDL and significant improvement in GSH-Px, SOD, TP, albumin and T3. Also, Elkomy and Elghalid, (2014) found that plasma TP, albumin and TAC were gradually increased while, plasma total lipids, cholesterol and lipid peroxidation activity and the ALT and AST enzymes activities were gradually and significantly decreased in MSS groups compared to the control.…”
Section: Blood Analysismentioning
confidence: 99%
“…These effects can be due to the combination of GS oil available to decreased absorbed crude fat. Also, Benzie (2003) and Ngamukote et al (2011) Abdallah et al (2017 who reported that GS extract has plenty of antioxidant substances that have decreasing effect on LDL and increasing effect on HDL and significant improvement in GSH-Px, SOD, TP, albumin and T3. Also, Elkomy and Elghalid, (2014) found that plasma TP, albumin and TAC were gradually increased while, plasma total lipids, cholesterol and lipid peroxidation activity and the ALT and AST enzymes activities were gradually and significantly decreased in MSS groups compared to the control.…”
Section: Blood Analysismentioning
confidence: 99%
“…This means SALE supplementation alone was not enough to lower cholesterol content to below control. Compounds that play a role in lowering cholesterol might be alkaloids and non-alkaloids (Santoso et al, 2010), saponins (Son et al, 2007), polyphenol (Ngamukote et al, 2011;Zang et al, 2006), flavonoid (Shrime et al, 2011). Patil et al (2010) reported that the reduction of cholesterol and triglycerides by alkaloids were in part caused by the reduction of lipogenic enzymes activities and increased bile acid excretion in feces.…”
Section: Levels Of Fat Protein and Cholesterol Meatmentioning
confidence: 99%
“…Ngamukote et al (2011) [51] suggested that gallic acid, catechin, and epicatechin might bind to TDCA and thus modulate the concentration of that BA in the gastrointestinal tract. Another study conducted in rats indicated that some dietary polyphenols, e.g., catechin, might reduce fecal BA, DCA and LCA [3].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%